Safari Qira’ah wa Ta’lim: Peningkatan Literasi Al-Qur’an di Desa Glingseran Kecamatan Wringin Kabupaten Bondowoso - Abd. Basid; Ahmad Maulidin; Deki Febrian; Kusyairi Kusyairi (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2026)
This program aims to enhance accurate Qur’anic reading skills, reinforce religious understanding, and foster community participation in sustainable Qur’anic education. The community service methodology employed a structured approach, including needs assessment, program planning, instructional implementation through lectures, discussions, and hands-on practice, as well as supporting activities, monitoring, and evaluation based on observations, competency tests, and participant feedback. The findings indicate a significant improvement in participants’ ability to read the Qur’an with proper tajwid, increasing from approximately 50% prior to the program to 85% after its implementation, along with improved basic comprehension of Qur’anic content among 75% of participants. The program also strengthened the roles of Qur’anic teachers, religious leaders, parents, and the broader community in creating a participatory Qur’anic learning ecosystem. From a policy perspective, these findings highlight the need for support from local governments, religious institutions, and relevant stakeholders in developing community-based Qur’anic literacy programs, enhancing the capacity of Qur’anic instructors, providing adequate learning facilities, and establishing independent learning groups as a strategy for sustaining religious education at the village level.